Worldwide evolution of equine RVA: four voices, one story - Miño, Samuel; Barrandeguy, Maria Edith; Parreño, Viviana (2019)
In this work, we used a Bayesian approach, together with all the information that was available in databases, to study the evolution of equine RVA.